2017
DOI: 10.1038/onc.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cyclooxygenase-2 overexpression induced spontaneous hepatocellular carcinoma formation in mice

Abstract: Cyclooxygenase (COX)-2 is upregulated in hepatocellular carcinoma (HCC). However, the direct causative effect of COX-2 in spontaneous HCC formation remains unknown. We thus investigate the role and molecular pathogenesis of COX-2 in HCC by using liver-specific COX-2 transgenic (TG) mice. We found spontaneous HCC formation with elevated inflammatory infiltrates and neovessels in male TG mice (3/21, 14.3%), but not in any of male WT mice (0/19). Reduced representation bisulfite sequencing (RRBS) and gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 44 publications
1
88
0
Order By: Relevance
“…Previous studies have also revealed that COX-2 can be induced by various stimuli, including hypoxia (15,16). In the context of HCC, COX-2 expression in tumour tissues is closely associated with the spontaneous initiation, development and treatment effects of HCC (17)(18)(19). As the predominant product of COX-2, prostaglandin E2 (PGE2) can achieve diverse biological effects primarily through its binding to a family of receptors to promote angiogenesis, cell survival and the metastasis of cancer cells (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also revealed that COX-2 can be induced by various stimuli, including hypoxia (15,16). In the context of HCC, COX-2 expression in tumour tissues is closely associated with the spontaneous initiation, development and treatment effects of HCC (17)(18)(19). As the predominant product of COX-2, prostaglandin E2 (PGE2) can achieve diverse biological effects primarily through its binding to a family of receptors to promote angiogenesis, cell survival and the metastasis of cancer cells (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that enhanced COX-2 expression in hepatocytes is sufficient to induce HCC, and its inhibition may provide a potential approach for preventing and treating liver cancer. 36 COX-2 and PGE2 levels were both significantly decreased following Tv1 treatment in 1MEA cells (Fig. 2b).…”
Section: Discussionmentioning
confidence: 82%
“…COX-2 is overexpressed in many premalignant, malignant, and metastatic cancers, including HCC, and is therapeutically targetable. 36,37 COX-2 expression is undetectable in most normal tissues, and is highly induced by pro-inflammatory cytokines, mitogens, oncogenes and growth factors. The tumorigenicity of 1MEA cells is associated with human growth factor (HGF) upregulation, which promotes EMT and carcinogenesis via upregulating COX-2 and Akt.…”
Section: Tv1 Inhibited Cox-2 Expression and Bioactivitymentioning
confidence: 99%
“…Reported to be downregulated in COX-2 induced hepatocellular carcinoma, where it might act as a tumor suppressor (H. Chen et al, 2017) DUSP26 Acts a tissue specific tumor suppressor and downregulation of the gene has been linked to tumorigenesis (Patterson, Brummer, Daly, & O'Brien et al, 2010)…”
Section: Znf426mentioning
confidence: 99%